A history of Southeast Asia critical crossroads - Reid, Anthony 1939- (Chichester, West Sussex John Wiley & Sons Inc., 2015)
"Incorporates environmental, social, economic, and gender issues to tell a multi-dimensional story of Southeast Asian history from earliest times to the present"-- Provided by publisher.
Includes bibliographical references and index.
Keywords: Southeast Asia -- History; Southeast Asia -- Foreign relations